Pengaruh Tingkat Sosial, Ekonomi Masyarakat Kepulauan dan Minat Belajar Terhadap Prestasi Belajar pada Pembelajaran Ekonomi Siswa Kelas X SMAN 12 Takalar - Nurbaeti, Nurbaeti; Nurdin, Nurdin; Syarifuddin, Syarifuddin (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the influence partially and simultaneously between the socio-social level, community economy, and learning interest on the economic learning achievement of grade X students of SMAN 12 Takalar and to find out which variables are dominant on the economic learning achievement of grade X students of SMAN 12 Takalar. This research approach uses quantitative research. The place of research was carried out on grade X students of SMAN 12 Takalar with a population of 64 students, the technique used was saturated sampling so a sample of 64 students data collection techniques using capacitors, observation and documentation and data analysis techniques using multiple regression. The results of the study are as follows; 1). Social Level (X1) has a positive and significant effect on Learning Achievement in Economics Learning of Class X Students of SMAN 12 Takalar.2). The Economics of the Archipelago Community (X2) has a positive and significant effect on Learning Achievement in Economics Learning of Class X Students of SMAN 12 Takalar.3). Student Learning Interest (X3) has a positive and significant effect on Learning Achievement in Economics Learning of Class X Students of SMAN 12 Takalar.4). Social Level (X1), Archipelago Community Economy (X2) and Student Learning Interest (X3) together affect Learning Achievement (Y). in Economics Learning for Class X Students of SMAN 12 Takalar. 5). The most dominant variable affecting Learning Achievement in Economics Learning of Class X Students of SMAN 12 Takalar is the Economics of the Archipelago Community.